Broadband tunable terahertz cross-polarization converter based on Dirac semimetals. (10th June 2019) - Dai, Linlin; Zhang, Yuping; Zhang, Huiyun; F. O'Hara, John
Abstract: We have investigated a single-layer metamaterial based on bulk Dirac semimetals (BDSs) that features tunable, broadband terahertz cross-polarization conversion in transmission mode. This effect can be actively tuned by changing the Fermi energy of the BDSs with no change to the geometry of the resonators. Tunability of the broadband polarization conversion is observed in the 3.82–7.88 THz range, over which the polarization conversion rate mostly remains above 80%. The proposed design offers a potentially effective approach to developing active terahertz polarization control devices for terahertz imaging, sensing, and communications.